PHYSICAL THERAPY FOR SCOLIOSIS IN ADOLESCENTS (Physical Culture and Sport: Scientific Perspective, 2024)
Scoliosis is one of the most common diseases of the musculoskeletal system, which is characterized by a curvature of the spine accompanied by its rotation around its own axis. This disease is often diagnosed in adolescence, when the body undergoes intensive physical development. Today, scoliosis is recognized as one of the urgent health problems of the younger generation, as the number of children and adolescents diagnosed with this pathology increases every year. Such a trend puts on the agenda the need to find new approaches to the correction of the state of health and prevention of further progression of the disease. Physical therapy is one of the key methods of both treatment and prevention of scoliosis, especially in adolescents, since it is at this age that the development of the musculoskeletal system undergoes significant changes. The main goal of physical therapy for scoliosis is not only to correct the existing curvature of the spine, but also to prevent its further progression. One of the main tasks of physical therapy is to teach patients the correct posture and the correct movement pattern in everyday activities, which significantly reduces the load on the spine. Exercises aimed at strengthening the muscles of the trunk and abdomen, as well as work on stabilizing the pelvis, contribute to the improvement of muscle coordination. It not only helps to correct the deformity, but also significantly improves the endurance and mobility of the body. In addition, physical therapy is not limited to the correction of spinal deformity. Its important goal is also to improve the patient's general state of health. This involves increasing physical activity, which helps strengthen the cardiovascular system, improve metabolism, and also support the normal functioning of the immune system. Physical activity stimulates the body to recover and helps to strengthen it, which is important for the overall development of a teenager. It is important that all classes are conducted under the supervision of a qualified physical therapist who can correctly select the necessary exercises. This approach ensures the effectiveness of treatment, the safety of performing exercises and contributes to a long-lasting result.
Keywords: curvature of the spine; conservative methods; posture correction; musculoskeletal system; muscle corset